2011
DOI: 10.1111/j.1468-3156.2010.00619.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life: a survey of parents of children/adults with an intellectual disability who are availing of respite care

Abstract: Accessible summary This article describes the findings of a small‐scale survey investigating the quality of life of parents of children and adults with an intellectual disability who are availing respite care with a response rate of 38% (n = 49). The findings of the study which was conducted in 2008 on parents’ experience of respite care in an Irish setting indicated that: Demand exceeds supply and many parents face a lengthy wait gaining access to respite care Respite care was not necessarily associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 39 publications
3
25
1
3
Order By: Relevance
“…The finding that caring had a negative effect on parents' relationships with their spouses is consistent with previous research (e.g. Caples & Sweeney 2010). Caples & Sweeney (2010) reported that parents of children and adults with ID often had to socialise separately because of caring demands.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The finding that caring had a negative effect on parents' relationships with their spouses is consistent with previous research (e.g. Caples & Sweeney 2010). Caples & Sweeney (2010) reported that parents of children and adults with ID often had to socialise separately because of caring demands.…”
Section: Discussionsupporting
confidence: 92%
“…Increased opportunities for participation in leisure activities that resulted from caring for an adult with ID have also been reported by parents of children and adults with ID (e.g. Shearn & Todd 1997; Caples & Sweeney 2010). The restrictions in leisure activities that detracted from QOL reported in the current study (e.g.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Sixty-five percent of participants in their study reported perceived benefits or positive outcomes such as "personal growth/enhanced personal resources," "enhanced social network," and a "sense of fulfilment or pride" (p. 44). Recent research suggests that the majority of parents of children and adults with ID experience high levels of satisfaction and quality of life (Caples & Sweeney, 2010). Previously, it has been reported that caregivers of adults with ID experience rewards and gratifications as part of the caregiving role (Grant, Ramcharan, McGrath, Nolan, & Keady, 1998).…”
mentioning
confidence: 99%